Optimization of EDGE Terminal Power Amplifiers Using Memoryless Digital Predistortion - Ceylan, Nazim; Müller, Jan-Erik; Weigel, Robert (IEEE Transactions on Microwave Theory and Techniques, 2005)
This paper describes a lookup-table (LUT)-based digital predistortion system usable for enhanced data for global system for mobile evolution (EDGE) handset transmitters. The system is memoryless and capable of improving average efficiency and performance in terms of the leakage power at offset frequencies and error vector magnitude. The obtainable efficiency at maximum linear output power is comparable, but at backoffs superior to commercial EDGE power amplifiers (PAs). Minimum system requirements on word length and LUT size have been investigated, which shows that a LUT having approximately 500 coefficients and a system word length of 13 bits are sufficient for EDGE. The proposed system is simple compared to basestation implementations comprising PA memory compensation and can be easily implemented in handsets in order to improve the overall system performance. The effects of antenna mismatch on system performance have been investigated.
elib2cris::1512001600,ceylan2005
Keywords: linear circuits; mobile communication; power amplifiers; memoryless systems